Strategi Pengembangan Bisnis Konsultan Perkebunan Kelapa Sawit PT. Intan Internasional - Arief Sidik; Siti Jahroh; Asep Taryana (Lembaga Teewan Journal Solutions, 2026)
This study aims to formulate business development strategies for PT Intan Internasional, a palm oil plantation consulting company experiencing declining project coverage and client numbers during 2016–2024. The research employed qualitative and quantitative approaches using interviews, observations, questionnaires, and literature studies. Strategic analysis was conducted through PESTEL, Porter’s Five Forces, VRIO, Value Chain Analysis, Internal Factor Evaluation (IFE), External Factor Evaluation (EFE), SWOT, and Quantitative Strategic Planning Matrix (QSPM). The findings indicate that the external environment provides substantial opportunities through sustainability regulations, mandatory ISPO certification, EUDR implementation, digital transformation, Internet of Things adoption, drone utilization, and carbon trading development. However, the company also faces threats from intense competition, clients’ high bargaining power, internal research divisions of large plantation corporations, and the perception of consulting services as discretionary spending. The EFE matrix score of 3.195 demonstrates that the company has a strong capability to respond to external opportunities and threats. Therefore, PT Intan Internasional should strengthen expertise differentiation, expand sustainability and digital-based services, integrate advanced technologies, and emphasize operational efficiency and regulatory compliance to enhance long-term competitiveness in the national palm oil consulting industry. These strategies are expected to improve adaptability, client trust, market expansion, and sustainable corporate performance.